DEVELOPING TOPWORKSHEET AS STUDENTS’ DESCRIPTIVE READING WORKSHEET AT SMPN 21 MEDAN - Kezia Aurelia Sembiring; Neni Afrida Sari (Indonesian Journal of Social Science and Education (IJOSSE), 2026)
This study aims to develop Topworksheet as students descriptive reading worksheet at SMP Negeri 21 Medan. Data consisted of an analysis of students' needs, interests, and challenges in using Topworksheet as descriptive reading worksheet, sourced from 20 ninth-grade students at SMP Negeri 21 Medan. Techniques for collecting data included distributing questionnaires, conducting interviews, and documentation. Instruments used were interview sheets, printed documents, and questionnaires. This study involved six key stages of Borg and Gall method, which included: gathering data and information, analyzing the data, designing the product, expert validation, revising and finalizing the product. The result of gathering and analyzing data showed that students had low interest in descriptive reading text due to monotonous and unvaried worksheets. This data identified students’ necessity (85%), lacks (55%) and wants (65%) for an interactive worksheet, engaging worksheet to develop reading understanding. The material designing and revising stage resulted in the Topworksheet Web, which consists of interactive descriptive reading practices, utilizing Canva-based visualization and educational games, including a glossary and word search. The expert validation involved a lecturer and a teacher, was 87.2%, and 98.4%, achieving an "Excellent" category. Based on the high validation scores from the experts, it can be concluded that the final product, the Topworksheet Web, is a highly appropriate and effective students' descriptive reading worksheet tailored to the specific needs of students at SMP Negeri 21 Medan.